Safety assessment in workplace for electricity utility company in Malaysia - Thiruchelvam S.; Mohamed F.K.P.K.; Mustapha K.N.; Ghazali A.; Ishak R.; Hakimie H. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Electricity utility technical workforce are often exposed to risk, danger and hazards at workplace ranging from accidents, electrocution, electric shock, burns, coal dust and noise. Globally, electricity utility recorded the lowest occupational accidents compared to other sectors but the number of fatalities seems to be quite significant. These accidents cause personal loss to employees as well as financial loss to organizations and the economy. This study was conducted in a local electricity utility company with the main aim of assessing the relationship between awareness and compliance of occupational safety and health amongst the technical workforce. The variables utilized to measure occupational safety and health (OSH) compliance included job safety, co-worker safety, supervisor safety, management safety practices and satisfaction with the safety program. This study was done cross-sectionally by using 174 respondents from main arms of the utility such as generation, transmission, distribution and other related subsidiaries. Results indicated that OSH compliance relies upon co-worker safety, supervisor safety, management safety practices and satisfaction with the safety program. Dominant factors such as supervisor safety and satisfaction with the safety program have great implications towards OSH compliance. The implication of this study is defined by its contribution to the understanding of numerous ways management in an electricity utility could endeavor in its effort of increasing employees well-being based on the needs of the employees and organizations. BEIESP.